Implikasi Sosiologi Hukum terhadap Penerapan Izin Penutupan Jalan: Studi Kasus Penerapan Teori Hukum Sebagai Alat Rekayasa Sosial (Social Engineering) Roscoe Pound: Penelitian - Joshua Hamonangan Rafael Siahaan; Agusmidah; Dedi Harianto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the sociological implications of law concerning the application of road closure permits, utilizing the theory of law as a tool of social engineering as proposed by Roscoe Pound. While road closures are sometimes necessary for construction or specific events, they often result in significant social impacts. Through a sociological legal approach, this research examines how the law can be effectively used to balance public and individual interests in the context of road closures. Case studies are conducted to understand how this theory is applied in practice and its impact on society.